The ugly caterpillar - Sommer, Carl, 1930-; Budwine, Greg (Houston, TX : Advance Pub., 2000)
Speckles the spider and Crumbs the cricket think a caterpillar is too ugly to be their friend, but Annie the ant insists that something beautiful might be inside.
Keywords: Insects -- Fiction; Beauty, Personal -- Fiction; Conduct of life -- Fiction